Aspectos estruturais e históricos do regime de metas de inflação: a experiência brasileira no período de 1999-2018 - ROSAR, Orlando Oscar (2024)
This thesis analyzes the Inflation Target Regime (RMI), implemented in Brazil from 1999 to 2018. The historicity of the process of establishing the conditionalities of the Brazilian economy since the slowdown in economic growth from the middle of the decade was highlighted 1970 and the derogation of the import substitution process, which produced the reprimarization of the export agenda and the growing support and appreciation of financial wealth maintained by the public fund, based on the operationalization of monetary policy. The RMI was analyzed as a mechanism constituted from the processes of determining the operating logic of the capitalist economy inserted in the global system, therefore identifying its contradictions and political, economic and social impacts in Brazil, in the defined period, in which the implementation of the new exchange rate anchor, based on the following hypothesis: the appreciation of wealth in the financial sphere conditions the macroeconomic policy of National States to a framework of permanent monetary and fiscal restrictions as evidenced in the Brazilian experience. To this end, research was carried out on expenditure indicators in relation to GDP and total expenditure. Data analysis made it possible to explain the reduced degree of autonomy of the drivers of economic policy to implement measures that could lead the country to economic growth with some degree of social inclusion, through public policies to meet basic and fundamental needs: employment, education, health, social security and assistance, in addition to economic infrastructure that would allow the reduction of inequality. This picture reflects, from an empirical point of view, the materialization of the new macroeconomic consensus, subordinating fiscal policy to monetary policy. The first was responsible for producing the resources necessary to maintain the debt/GDP ratio, whatever the interest rate. On the other hand, the execution of the second maintained a high level of interest rates, officially justified as necessary to control inflation, considered by orthodoxy as demand inflation. The analysis of the dynamics imposed by the RMI exposed the foundations of orthodox economic policy, the Keynesian and regulationist criticism and the Marxist opposition with the aim of elucidating the process of advancing financialization, not as an anomaly of capitalist development, but, above all, as an integral part of the totality expressed in the historical process of capital accumulation. In the contemporary period, the orthodox perspective remained hegemonic in Brazil, even when its formulations make evident its detachment from the concrete reality of developing countries, in which sectors of society seek to reduce economic and social inequality. It ends by emphasizing the historical need to overcome the contradiction between capital and labor and contain the process of environmental destruction, from the perspective of building economic, political, social and cultural foundations towards socialism.